Kaleidoscope of the History of Islamic Education in Aceh in the 16th - 21st Century - Imran (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
The kaleidoscope of the history of Islamic education in Aceh from the 16th to the 21st century depicts a colorful and complex journey, influenced by historical events, and political, social, and cultural changes. Just as a kaleidoscope changes the picture but retains its core elements, so too does Islamic education in Aceh continue to develop by integrating traditional values with modern demands. In the history of Islamic education in Aceh, as in the picture created in the kaleidoscope, we see continuous changes in the development of Islamic education but still involving core elements such as the role of ulama, pesantren, and strong Islamic values. It reflects a unique and complex journey, one that continues to incorporate traditions and adaptations to achieve broader and more relevant educational goals.